Una cuestión de lenguaje - Chantal Maillard (Universitat de Barcelona, 2010)
A maternal thinking is the one which gives us the possibility of acting and conceiving at the same time; it is a double conception produced within thinking and matter, because where love germinates there is no difference between matter and what, like a mirror, gives us an account of it. When being, loving and thinking are different things, we talk about justice where we should talk about humanity, and we talk about tolerance where we should talk about respect. At the same time, we educate our children in the exercise of their own and of distributive ethics. When we consider that love and thought are two different things it is not difficult to believe that wars, occupations, rapes, and all kind of attacks on the freedom of all of us have some kind of legitimacy. However, is it possible to dissociate ethical behaviour from love?